Causal effects of systemic lupus erythematosus on endometrial cancer: A univariable and multivariable Mendelian randomization study - Wan, An; Zhao, Wei-Dong; Tao, Jin-Hui (Frontiers in Oncology, 2022)
Objective Systemic lupus erythematosus (SLE) has been observationally associated with endometrial cancer, but the causality remains unclear. Here, we investigated for the first time the causal links between SLE and endometrial cancer risk. Methods Univariable and multivariable Mendelian randomization (MR) analyses were conducted to disentangle the causality of SLE with endometrial cancer. Apart from the inverse-variance weighted (IVW) method as the primary MR estimate, three complementary MR techniques including weighted median, weighted mode, and MR-Egger regression in univariable MR were conducted to clarify the robustness of the causal estimate and mediation effects of the body mass index (BMI) and were investigated within multivariable MR-IVW and MR-Egger analyses. Results All univariable MR analyses consistently suggested that SLE has a protective effect on the risk of overall endometrial cancer (IVW: OR = 0.956, 95% CI = 0.932-0.981, P = 0.001) and endometrioid endometrial cancer (IVW: OR = 0.965, 95% CI = 0.933-0.999, P = 0.043). More compelling, after adjustment for BMI within the multivariable MR setting, the association between SLE and decreased risk of overall endometrial cancer was significantly stronger (IVW: OR = 0.952, 95% CI = 0.931-0.973, P = 9.58E-06). Conclusions Our findings provide evidence of a significant causal relationship between SLE and decreased endometrial cancer risk. Further understanding of the underlying mechanisms linking SLE with endometrial cancer is therefore needed.